Teaching the instep kick to beginning soccer players - Brown,E.; Narvaez,M. (coachesinfo.com)
Because of the difficulties encountered by many beginning players in performing the instep kick, which is the most powerful kick in the sport of soccer, it is important that coaches understand these problems and have a teaching scheme to facilitate the learning of this important soccer skill. The remainder of this article addresses a progression that has been previously successful in teaching the instep kick to many young athletes. Content: - What is the Instep? - Manual Guidance - Supported Kick - Leap-Kick - Independent Kicking - Straight Approach - Angled Approach - Diagnosing Performance Problems - Practice Strategy for Teaching the Instep Kick